Analysis of Production Factors Affecting Intercropping of Corn and Peanuts in The Pandemic Era (Case Study in Katikupialang, Patawang Village, Umalulu District, East Sumba, Indonesia) - Wiwiek Andajani; I Gusti Gede Heru Marwanto; Tutut Dwi Sutiknjo; Saptorini (Dwijendra University, 2021)
In national development in Indonesia, the agricultural sector is still a very decisive economic force, because around 100 million Indonesians work in the agricultural sector. During this pandemic, support is needed for economic recovery, including how to maintain the availability of sufficient food for the community. Efforts to support food security, among others, by increasing the use of land that is more optimal, and also reducing the risk of crop failure, including the intercropping farming system. The objectives of this study were (1) to determine the production factors that influenced the intercropping of corn and peanuts, (2) to determine the production factors (land area, seeds, fertilizers, drugs and labor) which had the most dominant influence on the intercropping of corn and peanuts. In determining the research area, East Nusa Tenggara deliberately chose East Nusa Tenggara, because it has criteria in accordance with the research objectives, namely Patawang Village, Umalulu District, East Sumba Regency, East Nusa Tenggara, where the staple food of most of the population is maize, and the sampling is done census, where the population is small so that all populations are taken as samples, namely 15 samples. The data analysis uses cost analysis, revenue analysis and income or profit analysis, while to test the hypothesis using: (1) multiple regression analysis, (2) multiple correlation analysis, and (3) partial correlation analysis. From the results of the discussion, it can be concluded that together the production factors of land area, seeds, fertilizer, medicines and labor affect the intercropping of corn and peanuts, and fertilizer is the production factor that most influences it. Suggestions for holding training in making good organic fertilizers, from livestock manure and can be an organic fertilizer business opportunity.